Brand Extension of Fast Moving Consumer Goods to Customers’ Perception - Budiono Hardjono; Tan Bee Ying (Faculty of Economics and Business, University of Pasundan, 2017)
The cost of launching a totally new product or brand is usually very high accompanied by the risk of failure in an overcrowded market. Therefore, brand extension strategy is used due to its built in advantages. This research examined in depth, the factors in a brand extension which influence to customer perception about the existing brand in fast moving consumer goods (FMCG) sector. Four variables such as brand fit, perceived quality, brand familiarity and customer innovativeness, were used to establish the relationship with the customers’ perception. A questionnaire was developed and distributed to 200 respondents from hypermarket FMCG products’ consumers in Melaka city. It was found that in the context of personal hygiene products, only brand fit and perceived quality have a strong influence on the customer perception. Marketer should, however, carefully to evaluate their extension especially for local brand since not all factors in this extension significantly influence the customer perception.